The Effect of Digital Game-Based Learning on Learning Motivation and Performance Under Social Cognitive Theory and Entrepreneurial Thinking - Chen, Chia-Chen; Tu, Hsing-Ying (Frontiers in Psychology, 2021)
This study aims to investigate the effects of students’ learning motivation and learning performance in a digital game-based learning setting and the structure of competition. This study uses Social Cognitive Theory, which emphasizes the bidirectional effects between personal factors, environmental factors, and behavior. We use the emotional state as the personal factor, social support as the environmental factor, learning performance as behavior. We also use self-efficacy and learning motivation as the mediating factors in the model. Data samples were collected from approximately 600 students in junior high schools in Taiwan. The students learned via either application or conventional lectures in three groups. The Control Group (CG) learned the course through a conventional learning approach. The Experimental group 1 (EG1) learned by a digital game, while Experimental Group 2 (EG2) learned through the digital game in combination with a structure that involved competing and entrepreneurship with classmates. The result of this research shows that the emotional state negatively affects learning motivation and self-efficacy, that self-efficacy will positively affect learning motivation, social support will positively affect self-efficacy, and self-efficacy and learning motivation will both positively affect learning performance. In addition, this research certifies previous works that entrepreneurs prefer to be more aggressive in competitions, have a high demand for accomplishment motivation, and are more likely to facilitate competitive over non-competitive environments.